Una selección bibliográfica sobre el método AICLE (Aprendizaje Integrado de Conocimientos curriculares y Lengua Extranjera) - Almudena Fernández Fontecha (Universidad de La Rioja, 2013)
This work is a selected bibliography on the method of second/foreign language learning called Content and Language Integrated Learning (CLIL). Its main objective is to aid those who are interested in the theoretical part of the method as well as those interested in its implementation. The main corpus of this bibliography consists of a selection of articles, book chapters, books, reports from conferences and symposia, videos, and a list of websites dealing with this method.